Toward a Statutory Approach to Sovereign Debt Restructuring : Lessons From Corporate Bankruptcy Practice Around the World - Bolton, Patrick (IMF Working Papers; Working Paper ;, 2003)
This paper provides an overview of key elements of Corporate Bankruptcy Codes and Practice around the world that are relevant to the debate on Sovereign Debt Restructuring. It highlights four components common to most bankruptcy reorganization institutions: a stay on debt collection efforts to prevent a costly run for the assets, broad enforcement of absolute priority, majority voting among creditors on the proposed reorganization plan, and new higher priority financing to keep the firm going while its liabilities are restructured. The paper argues that these components ought to be present in any sovereign debt restructuring procedure.